Inequality and Hunger in Peru: 2001-2017 - Narváez Liceras, Alejandro (2020)
Both inequality and hunger are the main challenges of Peru. Since the reestablishment of democracy in 2001, the Peruvian economy has seen high growth rates, above those of other economies nearby. However, the benefits of democracy and the recent economic surge have been very modest and insufficient for the majority of the Peruvian people. Inequality still remains very high, being its main consequences, poverty and the rise of hunger in the country. Our hypothesis, therefore, is that the profits of the economic boom in 2001-2017 has not benefited all Peruvians. This paper examines the impact of this economic rise on inequality and hunger. And, finally, thanks to recent experiences, it explores new public policies and strategies that may be implemented in order to reduce the heightened inequality and to erradicate hunger in Peru.